Time analysis for the IAAF World Championships London 2017 steeplechase men's - Hanley, B.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
The men`s steeplechase final took place on August 8th on a cool evening. The medallists had all won their respective heats coming into the final, with the Olympic Champion, Kirputo, finishing one place higher than in the previous World Championships in 2015. Jager, the silver medallist from the 2016 Olympics, finished third behind Elbakkali, the Moroccan 21-year-old, who achieved a podium position for the first time in a global final having finished fourth in the Olympic final. Jager`s World Leading time of 8:01.29, set the previous month, was not threatened during this tactical race, and only Matthew Hughes, who finished 6th, set a season`s best time. The results for all finishers are shown. (Attention! registration on the IAAF site is required for downloading)